Oxidative stress induces meiotic defects of oocytes in a mouse psoriasis model - ZhiQin Zhang (Cell Death and Disease, 2022)
Abstract Psoriasis, an immune-mediated inflammatory disease, is associated with poor pregnancy outcomes. Emerging evidence indicates that these defects are likely attributed to compromised oocyte competence. Nevertheless, little is known about the underlying associated mechanisms between psoriasis and poor oocyte quality. In this study, we construct an imiquimod-induced chronic psoriasis-like mouse model to review the effects of psoriasis on oocyte quality. We discover that oocytes from psoriasis-like mice display spindle/chromosome disorganization, kinetochore-microtubule mis-attachment, and aneuploidy. Importantly, our results show that melatonin supplement in vitro and in vivo not only increases the rate of matured oocytes but also significantly attenuates oxidative stress and meiotic defects by restoring mitochondrial function in oocytes from psoriasis-like mice. Altogether, our data uncover the adverse effects of psoriasis symptoms on oocytes, and melatonin supplement ameliorates oxidative stress and meiotic defects of oocytes from psoriatic mice.